Obesity and Weight Change in Two United Kingdom Male Prisons. (October 2019) - Choudhry, Khurshid; Armstrong, David; Dregan, Alexandru
Prisoners' weight and waist circumference were measured 6 and 12 months after imprisonment. Variables known to be associated with differences in lifestyle behaviors and obesity were considered as covariates in the study. A total of 367 prisoners were recruited into the study at baseline, with 116 of these having dropped out of the study from the 6-month to the 12-month follow-up. The obesity prevalence rate increased 50% from baseline (16%) to the 6-month follow-up (24%). Obesity prevalence rates then declined 4-fold from the 6-month (24%) to the 12-month follow-up (6%). While time in prison was associated with an increase in body mass index, this effect was influenced by intrinsic prisoner characteristics, extrinsic factors, and the prison regime.